Analisis Kesulitan Siswa Sekolah Dasar pada Pembelajaran Geometri: Tinjauan Literature Review - Nia Aprilia; Silvia Fadila; Muhammad Hanafi; Yanti Fitria; Afriza Media (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
One of the areas of mathematics that studies the concept of flat and spatial shapes is geometry. Thus, in elementary school, geometry concepts are taught gradually in concrete, semi-concrete, and abstract forms. The research method using literature review. The results show that there are many reasons why many students in elementary school face difficulties in learning geometry materials. Therefore, this study will investigate the various reasons why students face difficulties in learning geometry materials.